A noteworthy new natural hybrid in the genus Oerstedella Rchb.f. (Orchidaceae: Laeliinae) - Pupulin, Franco (2016)
T h e n a t u r a l h y b r i d O e r s t e d e l l a x m o n t e v e r d e n s i s (O . e n d r e s i i x O . e x a s p e r a t a ) , f r o m t h e Monteverde area, Cordillera de Tilarán, and from the northern slopes of the Cordillera de Talamanca, Costa Rica, is described and illustrated. The flowers show intermediate characters between the putative parents. Sepals and petals are pale golden brown, and the lip white flushed with violet. The new natural hybrid is similar to O. endresii in the verrucose stems, the glabrous abaxial surface of the sepals and the entire mar- gins of the lateral lobes of lip; it is similar to O. exasperata in vegetative architecture, as well in the narrow isthmus of the lip and the prominent central keel of the midlobe.